Desarrollo de la lateralidad y su incidencia en la técnica del golpeo con el borde externo del pie no dominante en los niños de 8 a 12 años del club deportivo especializado formativo ¨Dr. José Cevallos Ruiz Yaguachi - Albán Guevara, Marcos Alexander (2022)
Laterality is the specific dominance of one of the cerebral hemispheres, which will determine whether the individual will be right-handed or left-handed. The predominance or preference of one cerebral hemisphere exerts dominance in the effective and more frequent use of one lateral half of the body over the other, which is why it is classified as homogeneous and crossed laterality. Therefore, it has repercussions on the maturation of the nervous system when performing sports and effectively on the athlete's own performance, having an implication in sports practice. The training of the non-dominant foot allows an improvement both in this foot and in the dominant one, and it can be even greater than training with the dominant side in the execution of the striking technique with the outer edge of the foot. The objective was to determine the incidence of the development of laterality in the technique of striking with the external edge of the non-dominant foot in children from 8 to 12 years of the Specialized Formative Sports Club ¨Dr. Jose Cevallos Ruiz ¨Yaguachi. The methodology of this research is fundamentally non-experimental, with a field and bibliographic modality. An observation sheet and the interview were used. The study sample consisted of 16 players and 2 coaches. According to the results obtained, it was identified that the players have crossed laterality, therefore an exercise guide was developed to improve the laterality in the hitting technique with the external edge of the non-dominant foot. Therefore, it can be concluded that the development of laterality does affect the striking technique with the outer edge of the non-dominant foot in children from 8 to 12 years of the Specialized Formative Sports Club ¨Dr. Jose Cevallos Ruiz